2008
DOI: 10.1007/s12253-008-9130-0
|View full text |Cite
|
Sign up to set email alerts
|

Correliation Between Osteopontin Protein Expression and Histological Grade of Astrocytomas

Abstract: Osteopontin is a ligand for the integrin proteins, which are cell surface receptors that mediate the physical and functional interactions between a cell and the extracellular matrix. The expression of osteopontin is reportedly increased in a number of transformed cell lines and tumor tissues. Furthermore, increased expression of osteopontin results in some infiltrative features of tumors. The aim of the study is to demonstrate that expression of osteopontin in human astrocytomas correlates with histological tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…We found significant up-regulation in the expression of 6 out of 7 genes in the tumors induced by HRasV12/AKT in and Ngn2 (Supplementary Figure 6). Among the 6 up-regulated genes, SPP1, which has been suggested as a diagnostic marker to distinguish ATRT from PNET and medulloblastoma (34) and as grade indicator of glioma (35), showed the greatest up-regulation (6.6 fold). The pattern of gene up-regulation combined with the histological features suggest that the tumors induced by HRasV12/AKT in combination with Ngn2 or NeuroD1 are ATRT-like tumors.…”
Section: Resultsmentioning
confidence: 99%
“…We found significant up-regulation in the expression of 6 out of 7 genes in the tumors induced by HRasV12/AKT in and Ngn2 (Supplementary Figure 6). Among the 6 up-regulated genes, SPP1, which has been suggested as a diagnostic marker to distinguish ATRT from PNET and medulloblastoma (34) and as grade indicator of glioma (35), showed the greatest up-regulation (6.6 fold). The pattern of gene up-regulation combined with the histological features suggest that the tumors induced by HRasV12/AKT in combination with Ngn2 or NeuroD1 are ATRT-like tumors.…”
Section: Resultsmentioning
confidence: 99%
“…4B and C). Because the product of one of these genes ( Spp1 ) has been suggested as diagnostic marker to distinguish AT/RTs from medulloblastoma (28) and as glioma grade indicator (29), we tested its expression at the protein level. Immunostainings confirmed the differential Spp1 expression (table in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional regulation of OPN is complex and involves multiple pathways, including AP-1, Myc, v-Src, Runx/CBF, TGF-β/BMPs/Smad/Hox, and Wnt/β-catenin/APC/GSK-3β/Tcf-4 (29). OPN expression has been found to correlate with tumor progression in astrocytoma with high levels in GBM (33)(34)(35). OPN levels detected by immunohistochemistry identified that high cytoplasmic OPN expression correlates with poor patient survival (36).…”
Section: Cancer Epidemiol Biomarkers Prev; 19(6) June 2010mentioning
confidence: 99%